Radiographic and ultrasonographic findings in a dog with emphysematous pyometra - Mattei, Chiara (Acta Vet Scand, 2018)
BACKGROUND: Emphysematous pyometra is a rare canine disease characterized by gas-forming bacteria infecting the uterus and causing an accumulation of both gas and infectious exudate in the uterine lumen. While radiological features of emphysematous pyometra have been previously described in dogs, the ultrasonographic appearance has not been reported. CASE PRESENTATION: A 7-year-old intact female Labrador Retriever was presented because of a 1 day history of vomiting, anorexia, mild polyuria/polydipsia and signs of fatigue. On physical examination the dog had a swollen vulva with a sparse amount of yellow discharge. Lateral and ventrodorsal radiographs showed a dilated predominantly gas-filled tubular structure located in the mid and cranial abdomen traversing from left to right and ending dorsally at the level of the 12th thoracic vertebra. A small intestinal ileus was initially suspected. Following the radiographic examination, abdominal ultrasound was performed. In the left mid and caudal abdomen there were two thin-walled gas-containing tubular structures. One had the typical layered appearance of an intestinal wall and represented the descending colon. The second structure had a similar thickness but homogenously hypoechoic wall and contained gas and echogenic fluid in the lumen. By use of several positional changes of the dog aiming to alter the location of the intraluminal gas, the second structure was traced to the right ovary cranially and the uterine body caudally, confirming that the structure was the right uterine horn. A final diagnosis of emphysematous pyometra was made. CONCLUSION: Ultrasound can be used as a non-invasive diagnostic method to differentiate between small intestinal ileus and emphysematous pyometra.